Pengaruh Gaya Kepemimpinan Tranformasional Dan Transaksional Terhadap Komitmen Organisasi Dengan Budaya Organisasi Sebagai Variabel Intervening Pada SMK Pawyatan Daha 3 Kediri - Erik Sumarsono; Imam Baehaki (Universitas Islam Kadiri, 2022)
The realization of organizational commitment becomes a problem in achieving organizational goals. The failure to realize organizational commitment is caused by the leadership never evaluating the results that have been achieved and the commitments made are not based on a clear consensus, and even though there is a consensus it is not implemented consistently and brings consequences as a result. an organizational culture. Researchers chose research at SMK Pawyatan Daha 3 Kediri because as an organization or educational institution that is starting to grow and develop and try to maintain its existence in the midst of competition between organizations. By experiencing two periods of leadership and having a strong organizational culture. Based on the above background, researchers are interested in conducting research with the title